Black Games Studies (Play Story Press, 2026)
Black Game Studies introduces the work of game makers from the African diaspora through academic scholarship, personal narratives and a catalog of works. It aims to provide a foundation from which researchers, designers, developers, game historians and others can draw an understanding of patterns, present practice, and a potential afro-future. Its works to make more visible, through aggregation and showcase, the creative contributions of Black game makers. It is an effort to meet the need to diversify the game-making community by not only highlighting the work of Black people, but in creating an enduring archive of such work.